Efisiensi Pengelolaan Arsip Surat melalui Implementasi Sistem Informasi Berbasis Web - Susan, Dede; Aditiyawarman, Didih; Syafa’at, Arris (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The sffective and efficient management of mail archives is very important in supporting the smooth administration of an educational institution. At Al-Luthfi Plus Elementary School, Purwakarta Regency, the management of incoming and outgoing letters is still done manually, which can hinder the process of searching, security, and archive maintenance. Therefore, a web-based information system is needed that can improve accessibility, security, and efficiency in managing the letter archive. This research aims to develop and implement an information system that uses PHP and MySQL technology, which can speed up the mail management process, reduce the risk of data loss, and facilitate the search and grouping of mail archives. The research method used is descriptive analytic, with an interview approach to the principal, admin, and staff to explore their needs, observation of the current management process, and literature study to explore related theories. The results show that the developed system successfully presents features such as letter classification, search, data security, and database backup/restore features that improve system efficiency and reliability. Evaluation through user feedback showed a significant improvement in the archive management process, with good user satisfaction. The implementation of this system is expected to support more transparent and effective school administration management, as well as accelerate the decision-making process.